The Moderating Effect of Acculturation Strategies on the Relationship Between Newcomer Adjustment and Employee Behavior - Hommey, Confidence; Ma, Jianhong; Asamani, Lebbaeus; Hanson, Priscilla (Frontiers in Psychology, 2020)
Acculturation begins when people find themselves in a cultural setting other than theirs and to demonstrate acceptable behaviors, one of two strategies is adopted, adapt to the new environment or retain ones own culture. On the basis of these two, four strategies have been proposed. The current paper examined the moderation effect of two of these acculturation strategies, Integration and Separation, on the relationship between Newcomer Adjustment, and Work Related Anxiety and Turnover Intentions. The study was in two folds, the first explored the moderation effect among new employees in general, notwithstanding their immediate past working experience; and the second part separated the sample based on two criteria: those prior to their current role were working in another firm (Work-to-Work Employees) and those who just come directly from school (School-to-Work Employees). The sample was made up of 250 employees who had spent not less than six months and not more than twelve months in their current role, drawn from the private banking and insurances firms in Ghana. The PROCESS analysis of the data revealed that integration moderated the relationship between newcomer adjustment and work related anxiety and turnover intentions among all samples. Separation moderated the relationships in all cases, but for the relationship between newcomer adjustment and turnover intentions in study one and among school-to-work employees. The evidence from this paper points to the fact that the acculturation strategy newcomers adopt has an effect on the relationship between their level of adjustment and some organizational outcomes; however, a slight difference exist if their immediate past engagement is considered.